Exploring the Effect of In Situ Urbanization on Youth Entrepreneurship in Suburban Areas with Low-Medium Development in China--A Way Forward to Sustainable Entrepreneurship Mechanism - Huang, Qingling; Rehman, Alam; Zeeshan, Muhammad; Ullah, Irfan (Frontiers in Environmental Science, 2022)
China’s traditional suburban urbanization pattern of “passively being centralized upstairs” is not ideal, so China is implementing human-centered new urbanization and urban-rural integration development strategy. Promoting employment through entrepreneurship is an effective way to solve the problem of long-term livelihood of land-lost farmers in China. There are few studies on entrepreneurship of land-lost farmers with the background of in-situ urbanization in the suburbs. Based on the field survey data of two suburban villages representing the low-medium level of development in China, this paper takes entrepreneurship of suburban youth as the research object and uses Logistic and Mlogit models to investigate the influences of psychological states of suburban youth on their entrepreneurship and the different entrepreneurial status during in-situ urbanization pattern from three aspects. The results show that: under in-situ urbanization pattern, the psychological states of suburban youth have significant and steady influences on their entrepreneurial behaviors; moreover, the satisfaction degree of land expropriation compensation has a partial mediation effect on suburban youth's judgment of future life. There are different effects of the three psychological states on the two entrepreneurial states. Therefore, urban governments at all levels in China should choose the suburban urbanization pattern according to local conditions and times changes, realize sustainable entrepreneurship of suburban land-lost farmers during their becoming citizens with keeping nostalgia.